Before the Museums Came. The Fine Arts in the Twin Cities - Harris, Leo J. (De Gruyter, 2012)
Before the Museums Came: A Social History of the Fine Arts in the Twin Cities gives an engaging portrayal of the fine arts scene of Minneapolis and St. Paul, Minnesota in the United States, spanning from the appearance of the earliest artists in 1835 to the opening of the first permanent museum, the Minneapolis Institute of Arts in 1915. Readers will learn about the institutions and organizations that were created in support of the fine arts, the early art exhibitions and events, and the collectors, dealers and artists whose efforts made all of that come to fruition. The text - enriched and supplemented by reproductions of artworks, photographs of various personages, exhibition venues, studios, art galleries, catalogues, and ephemera - presents a clear understanding of the period and breaks new ground for future scholars to research.